Raktarekhā - Daḷavī, Pradīpa (Manoramā Prakāśana, 2010)
Novel based on military operation and historical theme
Novel. - Includes bibliographical references. - Marathi in Devanagari-Schr
Keywords: Historical fiction; Marathi